2021
DOI: 10.1016/j.mex.2021.101228
|View full text |Cite
|
Sign up to set email alerts
|

Fractal dimension analysis: A new tool for analyzing colony-forming units

Abstract: The gold standard for quantifying bacteria both in routine diagnostics and in research is plating followed by count of colony-forming units (CFU). But, manual CFU counting on plates is time-consuming and subjective. We evaluated fractal dimension as a new methodology for evaluating CFU. Twenty fragments of expanded polytetrafluoroethylene (ePTFE) synthetic vascular prosthesis and 20 silicone prostheses were embedded in bacterial suspensions and incubated. The prostheses were then sown in solid culture medium a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
4
0
2
Order By: Relevance
“…We have also calculated the SRFs and demonstrated that they can be used as a new tool to investigate properties of green algae and also to classify them, based on the form of their SRF, within their families as currently algae of a given family are neither ordered nor organized [26,27]. Moreover, the SRFs can also be generated for other types of algae, namely, Macroalgae (red and brown) or Microalgae [26,27], as well as for many other diversified biological systems, such as the roots of plants [30] and their complexity [34], scaling time in biochemical networks [35], organization of ecosystems [36], human physiology and well-being [37], and microbial colonies [38]. We do hope that biologists working in different areas, and other natural scientists, find the SRFs useful in their work and apply them to different natural systems.…”
Section: Discussion Of the Obtained Resultsmentioning
confidence: 99%
“…We have also calculated the SRFs and demonstrated that they can be used as a new tool to investigate properties of green algae and also to classify them, based on the form of their SRF, within their families as currently algae of a given family are neither ordered nor organized [26,27]. Moreover, the SRFs can also be generated for other types of algae, namely, Macroalgae (red and brown) or Microalgae [26,27], as well as for many other diversified biological systems, such as the roots of plants [30] and their complexity [34], scaling time in biochemical networks [35], organization of ecosystems [36], human physiology and well-being [37], and microbial colonies [38]. We do hope that biologists working in different areas, and other natural scientists, find the SRFs useful in their work and apply them to different natural systems.…”
Section: Discussion Of the Obtained Resultsmentioning
confidence: 99%
“…Teknologi pengolahan citra digital telah banyak dikembangkan untuk membuat aplikasi dalam berbagai bidang, salah satunya adalah pemanfaatan teknologi citra digital dalam bidang biologi untuk analisis citra. Sebelumnya peneliti telah melakukan penelitian serupa yang bertujuan untuk menghitung koloni bakteri dan menghasilkan akurasi sebesar 94% dan peneliti menemukan bahwa beberapa koloni tidak terdeteksi karena terfilter saat preprocessing, sehingga peneliti melakukan penelitian lebih lanjut mengenai preprocessing Kata Kunci-Koloni, Pengolahan Citra, Preprocessing I. PENDAHULUAN Penelitian di bidang mikrobiologi terutama bakteri seringkali berpatokan pada penentuan jumlah koloni atau Colony Forming Units (CFUs) yang akurat [2]. Bakteri dapat ditumbuhkan dalam suatu medium agar dan akan membentuk penampakan berupa koloni.…”
Section: Perbandingan Metode Median Filtering Dengan Clahe Dalam Meng...unclassified
“…Standar emas untuk mengukur bakteri baik dalam diagnostik rutin dan dalam penelitian adalah pelapisan diikuti oleh jumlah unit pembentuk koloni (CFU). Namun, penghitungan CFU manual pada pelat memakan waktu dan subjektif [2]. Selain itu proses manual membutuhkan tingkat konsentrasi yang tinggi, sehingga jumlah koloni yang terhitung sangat dipengaruhi oleh kondisi fisik dan mental dari peneliti bidang mikrobiologi itu sendiri.…”
Section: Perbandingan Metode Median Filtering Dengan Clahe Dalam Meng...unclassified
“…After incubation, the plates were photographed with a digital camera (Cyber Shot W830 20.1MP, Sony, Japan) and analyzed with ImageJ ® software (http://rsbweb.nih.gov/ij/). Fractal dimension analysis was performed by the box-counting method (Figure 1) (Stolze et al, 2019;Nai et al, 2021).…”
Section: Twenty Silicone Prostheses Measuring 2 CM Diameter (Model Forma Malhas Compressivas E Produtos Hospitalaresmentioning
confidence: 99%